Peru : Staff Report for the 2010 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2010)
This 2010 Article IV Consultation highlights that growth in Peru decelerated sharply in 2009, owing to the global financial crisis, but remained positive at about 1 percent for the year, despite a few months in negative territory. Thanks to the strong buffers built in recent years, Peru was able to implement a significant monetary and fiscal policy response, which helped to avoid a credit crunch, support domestic demand, and sustain employment. The central bank injected substantial liquidity in the financial system and lowered the policy rate to an historic low of 1.25 percent.